2011
DOI: 10.1002/app.34799
|View full text |Cite
|
Sign up to set email alerts
|

The crystallization behavior and mechanical properties of polylactic acid in the presence of a crystal nucleating agent

Abstract: The crystallization behavior of polylactic acid (PLA) was studied in the presence of a crystal nucleating agent, ethylenebishydroxystearamide (EBH). The crystallization rate and crystallinity were significantly increased with addition of EBH. The isothermal crystallization halftime at 105 C was decreased from 18.8 minutes for neat PLA to 2.8 minutes for PLA with 1.0 wt % of EBH. The crystallinity of PLA with 1.0 wt % EBH was about 35% after 5-minute annealing at 105 C. Like neat PLA, the double melting peaks w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
88
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 140 publications
(94 citation statements)
references
References 37 publications
6
88
0
Order By: Relevance
“…He et al investigated the effect of phthalimide on PLA crystallization behavior, in which the addition of 0.3% phthalimide increased the crystallization of PLA. Tang et al reported that ethylenebishydroxystearamide improved the mechanical properties and crystallization behavior of poly( l ‐lactic acid) (PLA). Therefore, organic nucleating agents are expected to serve as efficient nucleation agents for the crystallization of PLA.…”
Section: Introductionmentioning
confidence: 99%
“…He et al investigated the effect of phthalimide on PLA crystallization behavior, in which the addition of 0.3% phthalimide increased the crystallization of PLA. Tang et al reported that ethylenebishydroxystearamide improved the mechanical properties and crystallization behavior of poly( l ‐lactic acid) (PLA). Therefore, organic nucleating agents are expected to serve as efficient nucleation agents for the crystallization of PLA.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, improving heat resistance has also drawn increasing attention in the area of PLLA modifications [3,[32][33][34]. The poor heat resistance, namely low HDT, arises from the low degree of crystallinity during thermal processing, ascribed to the extremely slow crystallization rate of PLLA.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there has been increasing interest in the development of biomass‐based plastics to alleviate global warming and other environmental burden. Considerable efforts have been made to substitute fossil resource‐based materials with materials from natural and crop resources 1–6…”
Section: Introductionmentioning
confidence: 99%